2015
DOI: 10.1186/s12970-015-0091-x
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis and exercise-associated hyponatremia in ultra-bikers and ultra-runners

Abstract: BackgroundExercise-associated hyponatremia (EAH), rhabdomyolysis and renal failure appear to be a unique problem in ultra-endurance racers.MethodsWe investigated the combined occurrence of EAH and rhabdomyolysis in seven different ultra-endurance races and disciplines (i.e. multi-stage mountain biking, 24-h mountain biking, 24-h ultra-running and 100-km ultra-running).ResultsTwo (15.4 %) ultra-runners (man and woman) from hyponatremic ultra-athletes (n = 13) and four (4 %) ultra-runners (four men) from the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 41 publications
5
44
0
4
Order By: Relevance
“…In summary, the primary etiology and pathophysiological mechanism underlying EAH in the present ultra-endurance athletes group was presumably overconsumption of hypotonic fluids in likely combination with non-osmotic arginin vasopressin secretion as we stated in our previous studies (Chlíbková et al, 2014;Chlíbková et al, 2015;Chlíbková et al, 2016).…”
Section: Comparison Of Hyponatremic and Normonatremic Finisherssupporting
confidence: 59%
See 2 more Smart Citations
“…In summary, the primary etiology and pathophysiological mechanism underlying EAH in the present ultra-endurance athletes group was presumably overconsumption of hypotonic fluids in likely combination with non-osmotic arginin vasopressin secretion as we stated in our previous studies (Chlíbková et al, 2014;Chlíbková et al, 2015;Chlíbková et al, 2016).…”
Section: Comparison Of Hyponatremic and Normonatremic Finisherssupporting
confidence: 59%
“…Racers, event staff and emergency medical service personnel should be educated about proper recognition and treatment of EAH (Bennett, Hew-Butler, Hoffman, Rogers, & Rosner, 2013;Hew-Butler et al, 2015;Wegelin & Hoffman, 2011). Recently, it was reported that in 2012/2013 11.5% of 113 ultra-endurance athletes from a number of different sports developed post-race hyponatremia (Chlíbková et al, 2015). This was an increase from previous research on this population in the Czech Republic in 2012 (5.7% of the 53 finishers) (Chlíbková, Knechtle, Rosemann, Žákovská, & Tomášková, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Cairns and Hew-Butler study (11), transient hypovolemic EAH preceded significantly higher elevations in CK in their limited sample size of runners during an ultraendurance race. In our recent study (14), we documented 6% cases of EAH with rhabdomyolysis in ultra-endurance runners (five men and one woman) and 0% in ultra-endurance mountain bikers. Fellmann et al (20) demonstrated that a 24-h running race caused more muscular lesions than a triathlon, where ultra-endurance cycling was a part of the event.…”
Section: Hematological Parameters Plasma Urea Plasma Creatinine Andmentioning
confidence: 79%
“…A 46-year-old female mountain biker won the "Czech Championship 24-h mountain biking race" in Jihlava (Case 3), a race with the highest number of participants from the series of 24-h mountain bike races held in the Czech Republic (14). The ultraendurance mountain bikers started at 12 p.m. on 18 May 2013 and finished at 12 p.m. on 19 May 2013.…”
Section: Racesmentioning
confidence: 99%